Legal aspects of gender balance on corporate boards in Germany: This document was requested by Policy Department C of the European Parliament - Katja Langenbucher (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
The German corporate governance code includes a recommendation as to diversity on corporate boards. Two draft bills on gender quotas are currently under way in legislative proceedings. However, the ruling coalition rejects those, advocating a flexible quota. The present study provides an overview on legislative proposals currently presented and on academic scholarship on the issue. Legal obstacles to the introduction of a fix quota under German law are discussed and the soft version of flexible quotas is advocated.
urn:nbn:de:hebis:30:3-314072
Keywords: 330; German constitutional law; German corporate governance codex; gender equality